Strategies for Surgical Approaches in Open Reduction Internal Fixation of Pilon Fractures. Issue 2 (February 2015) - Assal, Mathieu; Ray, Adrien; Stern, Richard
Abstract : Summary: Pilon or tibial plafond fractures usually result from high-energy injuries with rotation and/or axial compression. They occur in an area of relatively poor soft tissue coverage and frequently present a surgical challenge in deciding which incisions will be best for performing open reduction internal fixation. A variety of anterior and posterior approaches have been described based on the ease of fracture reduction and internal fixation with plates. Some of the incisions are fracture specific, that is, planned for a limited approach to the pilon. But in more complex cases, a wider exposure is indicated and thus more extensile approaches, both anterior and posterior, can be valuable. This review article will describe the different surgical approaches, focusing on their indication and technique.